2005
DOI: 10.1002/art.21270
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of chemokines and type 1 cytokines in the pathogenesis of hepatitis C virus–associated mixed cryoglobulinemia vasculitis neuropathy

Abstract: Objective. To examine the expression profiles of a large number of genes within typical vasculitic nerve lesions in patients with mixed cryoglobulinemia (MC) vasculitis in order to better characterize the molecules involved in cellular tissue activation and trafficking.Methods. The quantitative expression of 19 genes coding for cytokines, chemokines, and their receptors in the nerve lesions of 9 patients with hepatitis C virus (HCV)-associated MC vasculitis, 7 with idiopathic polyarteritis nodosa (PAN) (rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 23 publications
(27 reference statements)
1
52
0
Order By: Relevance
“…cytokines, including IFN-␥ and TNF-␣, in vasculitic nerve lesions (30). Chemokines and chemokine receptors involved in T cell and monocyte trafficking, such as Ccl3, Ccl4, and Cxcr3, were also significantly upregulated (30).…”
Section: Discussionmentioning
confidence: 99%
“…cytokines, including IFN-␥ and TNF-␣, in vasculitic nerve lesions (30). Chemokines and chemokine receptors involved in T cell and monocyte trafficking, such as Ccl3, Ccl4, and Cxcr3, were also significantly upregulated (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of T-cell abnormalities have been described, including a polarization toward Th1 subsets 17,19,38 and also a quantitative deficiency of circulating regulatory T cells. 20 B-cell depletion has been used in the treatment of patients with a number of different autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have shown that Th1/Th2 imbalance plays a central role in HCV-MC vasculitis. 19,38 It is important to emphasize that several factors can determine the fate of activated T cells, including type of antigen-presenting cells, costimulatory molecules, chromatin structure, and cytokines present in the local microenvironment of the cell at the time of stimulation. Interestingly, the data present here indicate that Th1 polarization can be reverted after treatment with rituximab, but only in complete responders of MC vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of HCV-related vasculitis is still controversial. Neutrophilic infiltration with leukocytoclastic changes typical of immune complex-mediated vasculitis has seldom been found, while the presence of lymphohistiocytic infiltrates suggests a T cellmediated pathogenesis and only a minor role for the humoral mechanisms in the formation of the vasculitic lesions (27)(28)(29). Along this line, relapses of HCV vasculitis after rituximab therapy were significantly higher in PAN compared to MC patients.…”
Section: Pan-type Vasculitis Associated With Hcvmentioning
confidence: 99%